A funç\~ao dos planos plurianuais no direcionamento dos orçamentos anuais: Avaliaç\~ao da trajetória dos PPAS no cumprimento da sua miss\~ao constitucional e o lugar do PPA 2020-2023 - Leandro Freitas Couto; José Celso Cardoso Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The purpose of the article is to assess how much the Multi-Year Plan (MYP) has managed to fulfill its constitutional mission to guide allocative decisions through the budget process. To this end, it discusses the functions of government planning, its relationship with public finances, to present the trajectory of the Plan since 2000, with the different functions that the instrument played. Based on these discussions, it presents the proposed changes for the Multi-Year Plan 2020/2023, seeking to demonstrate how they dialogue with this history and how they can strengthen or weaken the instrument, also highlighting the contributions of the National. The article indicates that the entire budgetary governance regime, including the general framework of fiscal policy and protection of financial expenses, influences the possibilities of making this connection in a way that can guide the preparation and execution of the budget. It is evident that MYP's approaches and functions need to be aligned in order to enhance the instrument's capabilities. However, a discussion that is limited to just one instrument tends to be limited and lead to wrong decisions, as is the proposal for extinction of the PPA.
Keywords: O21; H61; H11; H50; 330; government planning; multi-year plan; budgetary governance; public budget; multi-year plan 2020/2023